Representations of women’s epistolary writing in the framework of mass emigration from Asturias (1880-1936) - Martínez Martín, Laura (Cuadernos de Historia, 2023)
This work arises from the intersection of two necessities: the need to include the subordinate subjects of history in the historical discourse and the need to pay attention to personal sources. Thus, the focus is on the women who took part in the mass migrations of the late nineteenth century and the first third of the twentieth century and on the private letters that they exchanged with their loved ones. Correspondences that help us to know the representations of epistolary writing from the conception of letters as “representation of an absence” as well as “exhibition of one’s own presence”. Without forgetting the role played by these egodocuments as representation tools of women in the migration context